EMPLOYEE PERFORMANCE IN THE EDUCATION DEPARTMENT OF ASAHAN DISTRICT: THE IMPACT OF PERSONAL QUALITIES AND WORK MOTIVATION - Fitri Kumala Sari; Asnawi; Santoso, Didik; Batubara, Irpan; Safitri, Aini (Program Studi Manajemen Pendidikan Islam, 2025)
Abstract This research aims to determine (1) the magnitude of the influence of individual characteristics on improving employee performance at the Asahan district education office, (2) the magnitude of the influence of work motivation on improving employee performance at the Asahan district education office, and (3) the magnitude of the influence of individual characteristics and work motivation overall. together to improve employee performance at the Asahan district education office. The research method used is a quantitative type of correlational study with a correlative study pattern. The results of this research are presented (1) the magnitude of the positive and significant influence between individual characteristics on improving employee performance with a correlation coefficient rx1y=0.680. The effective contribution made by individual characteristic variables to enhance the performance of employees of the Asahan District Education Service is 68%, and (2) the magnitude of the positive and significant influence between work motivation and improving the performance of employees of the Asahan District Education Service with a correlation coefficient rx1y = 0.930. The effective contribution made by the work motivation variable to enhancing the performance of Asahan District Education Service employees is 93%, and (3) there is a positive and significant influence between individual characteristics and work motivation together by increasing the performance of Asahan District Education Service employees by a coefficient correlation of 0.990 and a joint effective contribution of 99%. This means that these two factors are very determining in improving employee performance. If these two factors are good, employee performance will be even better. Keywords: Individual characteristics, Work motivation, Employee performance